2011
DOI: 10.1093/infdis/jir186
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection and Hepatic Stellate Cell Activation Downregulate miR-29: miR-29 Overexpression Reduces Hepatitis C Viral Abundance in Culture

Abstract: HCV infection downregulates miR-29 in hepatocytes and may potentiate collagen synthesis by reducing miR-29 levels in activated HSCs. Treatment with miR-29 mimics in vivo might inhibit HCV while reducing fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 46 publications
5
117
0
Order By: Relevance
“…A number of cellular miRNAs have been found to regulate HCV infection (9,25,31,32). In response to IFN treatment, host cells initiate an antiviral defense mechanism that involves the induction of certain miRNAs that suppress viral mRNA replication and the inhibition of other cellular miRNAs that promote the viral life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A number of cellular miRNAs have been found to regulate HCV infection (9,25,31,32). In response to IFN treatment, host cells initiate an antiviral defense mechanism that involves the induction of certain miRNAs that suppress viral mRNA replication and the inhibition of other cellular miRNAs that promote the viral life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although IGF-I has also been shown to induce apoptosis in HSC, 50 in cooperation with PDGF-BB, it certainly functions as an important mitogen for hepatic myofibroblasts. 51,52 Accordingly, miR-29, shown to affect moderately HSC proliferation, 53 might be involved in HSC growth by posttranscriptional IGF-I synthesis control.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Serum miR-29a is significantly lower in patients with advanced liver cirrhosis than in healthy controls or patients with early fibrosis. 12 Further it has been shown that overexpression of miR-29 in murine HSC resulted in the downregulation of collagen expression 12,14 through a mechanism that directly targets the mRNA expression of ECM genes. These findings suggest that miR-29 may be an important therapeutic target in chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%